Implementasi Undang-Undang Tentang Yayasan Di Kabupaten Timor Tengah Utara - Randy Vallentino Neonbeni (Pusdikra Publishing, 2022)
This research was conducted in North Central Timor Regency regarding Foundation Legal Entities that have not made adjustments to the Foundation Articles of Association in accordance with Law No. 16/2001 and PP No. 2/2013 and as a result of the law if the foundation organ does not immediately make adjustments to the Foundation's Articles of Association based on laws and regulations, the institution cannot use foundation sentences. To achieve this goal, the author uses the technique of the approach of legislation (state approach) and concept approach (conceptual approach). The results of this study show that there are still many Foundation Legal Entities in North Central Timor regency that have not made adjustments to the Articles of Association of Foundation Legal Entities in accordance with the Foundation Law, in addition to the results of research, the author also found things that are factors that inhibit the implementation of Law No. 16/2001. These inhibitory factors include that many people do not know about the latest rules related to the foundation.